Prefusion F-specific antibodies determine the magnitude of RSV neutralizing activity in human sera - Ngwuta, Joan O; Chen, Man; Modjarrad, Kayvon; Joyce, M Gordon; Kanekiyo, Masaru; Kumar, Azad; Yassine, Hadi M; Moin, Syed M; Killikelly, April M; Chuang, Gwo-Yu; Druz, Aliaksandr; Georgiev, Ivelin S; et al. (Science translational medicine, 2015)
Respiratory syncytial virus (RSV) is estimated to claim more lives among infants <1 year old than any other single pathogen, except malaria, and poses a substantial global health burden. Viral entry is mediated by a type I fusion glycoprotein (F) that transitions from a metastable prefusion (pre-F) to a stable postfusion (post-F) trimer. A highly neutralization-sensitive epitope, antigenic site Ø, is found only on pre-F. We determined what fraction of neutralizing (NT) activity in human sera is dependent on antibodies specific for antigenic site Ø or other antigenic sites on F in healthy subjects from ages 7 to 93 years. Adsorption of individual sera with stabilized pre-F protein removed >90% of NT activity and depleted binding antibodies to both F conformations. In contrast, adsorption with post-F removed ~30% of NT activity, and binding antibodies to pre-F were retained. These findings were consistent across all age groups. Protein competition neutralization assays with pre-F mutants in which sites Ø or II were altered to knock out binding of antibodies to the corresponding sites showed that these sites accounted for ~35 and <10% of NT activity, respectively. Binding competition assays with monoclonal antibodies (mAbs) indicated that the amount of site Ø-specific antibodies correlated with NT activity, whereas the magnitude of binding competed by site II mAbs did not correlate with neutralization. Our results indicate that RSV NT activity in human sera is primarily derived from pre-F-specific antibodies, and therefore, inducing or boosting NT activity by vaccination will be facilitated by using pre-F antigens that preserve site Ø.